Role of the α7 Nicotinic Acetylcholine Receptor in the Pathophysiology of Atherosclerosis - Vieira-Alves, Ildernandes; Coimbra-Campos, Leda M. C.; Sancho, Maria; da Silva, Rafaela Fernandes; Cortes, Steyner F.; Lemos, Virgínia Soares (Frontiers in Physiology, 2020)
Atherosclerosis constitutes a major risk factor for cardiovascular diseases, the leading cause of morbidity and mortality worldwide. This slowly progressing, chronic inflammatory disorder of large- and medium-sized arteries involves complex recruitment of immune cells, lipid accumulation, and vascular structural remodeling. The α7 nicotinic acetylcholine receptor (α7nAChR) is expressed in several cell types involved in the genesis and progression of atherosclerosis, including macrophages, dendritic cells, T and B cells, vascular endothelial and smooth muscle cells (VSMCs). Recently, the α7nAChR has been described as an essential regulator of inflammation as this receptor mediates the inhibition of cytokine synthesis through the cholinergic anti-inﬂammatory pathway, a mechanism involved in the attenuation of atherosclerotic disease. Aside from the neuronal cholinergic control of inflammation, the non-neuronal cholinergic system similarly regulates the immune function. Acetylcholine released from T cells acts in an autocrine/paracrine fashion at the α7nAChR of various immune cells to modulate immune function. This mechanism additionally have potential implications in reducing atherosclerotic plaque formation. In contrast, the activation of α7nAChR is linked to the induction of angiogenesis and VSMC proliferation, which may contribute to the progression of atherosclerosis. Therefore, both atheroprotective and pro-atherogenic roles are attributed to the stimulation of α7nAChRs, and their role in the genesis and progression of atheromatous plaque is still under debate. This minireview highlights the current knowledge on the involvement of the α7nAChR in the pathophysiology of atherosclerosis.